Reductive Deamination by Benzyne for Deoxy Sugar Synthesis Through a Domino Reaction - Hwu, Jih Ru (ChemistryOpen, 2017)
Benzyne was developed as a reducing agent in the key step of converting amino sugars and ketoses into deoxy sugars, which occur widely in natural products. Many deoxy sugars exhibit antibiotic and anticancer activities, and furthermore, they play essential biological roles. By treatment with CS(2) and then Ac(2)O, amino sugars and ketoses were converted into the corresponding 1,3‐thiazolidine‐2‐thiones. In the key step, these intermediates were treated with 2‐trimethylsilylphenyl triflate (2.0 equiv.) and CsF (3.0 equiv.) in MeCN at 25 °C to produce acyclic enol acetates in 60–63 % yields. Saponification of the enol acetates with NaOMe/MeOH followed by intramolecular cyclization afforded the target 2‐deoxy sugars. The key step of the reductive deamination involved a domino 1,2‐elimination/[3+2]‐cycloaddition/retro [3+2]‐ring‐opening sequence. The generality of this new method was proven by the use of various substrates, including pentoses, hexoses, monosaccharides, disaccharides, aldoses, and ketoses.